“I Discovered I Love to Pray Alone Too”: Pluralist Muslim Women’s Approaches to Practicing Islam during and after Ramadan 2020 - Piela, Anna (Religions, 2021)
Public health guidelines implemented during the COVID-19 pandemic have changed the way many people practice religion. In the realm of Islam, practices from the margins—attending online mosques and prayer groups, or praying alone—suddenly became commonplace. This paper addresses the question: What religious processes have become more evident among pluralist Muslim women during the pandemic? Based on 34 open-ended online surveys completed by pluralist Muslim women living chiefly in the USA and the UK, our analysis evidences the existence of four narratives that reflect fluctuations in the intensity and type of religious practice. The first and most prominent narrative in our dataset conveys enthusiastic embrace of social-distanced practices; the second describes a profound sense of aberration impossible to overcome in spiritual ways. The third highlights that for some Muslims, the pandemic brought no changes, as they continued to be isolated from their communities. The fourth is focused on an affirmation of a “remote” sociality experienced online. While some respondents acknowledge the increased individuation in their religious practice, they also find fulfilment in collective, if transformed, sociality. The changes in social interaction have led to a re-evaluation of salient aspects of their religious identity or, alternatively, highlighted longstanding modalities of exclusion.